Mechanism of paraquat resistance – from the antioxidant enzymes to the transporters - Szigeti, Zoltán (Acta Biologica Szegediensis, 2005)
In this paper a review of the most important results on the paraquat resistance mechanism of weeds is given, with special respect on horseweed Conyza canadensis (L.) Cronq. There is no difference between susceptible and resistant plants in the activity of antioxidant enzymes and in the penetration of paraquat into the chloroplasts. The paraquat resistance is primarily based on higher expression of a putative amino acid/polyamine transporter which is responsible for the exclusion of paraquat into the vacuole in resistant horseweed.